Spanish word histories and mysteries English words that come from Spanish - Houghton Mifflin Company (Boston Houghton Mifflin, 2007)
"Spanish Word Histories and Mysteries: English Words That Come From Spanish tells 150 fascinating stories about words and expressions that have made their way from Spanish to English. Most of us know that English words like guacamole and salsa originated in Spanish, but there are many more English words and expressions that we would never suspect are Spanish until we take a closer look, including barbecue, breeze, embargo, hammock, hurricane, incommunicado, and vamoose. Even the English terms for some of the most basic foods come from Spanish, such as potato, tomato, chocolate, and vanilla." "Whether you are a student of Spanish, or just someone who loves words, you will enjoy discovering the surprising and unexpected Spanish roots of English in Spanish Word Histories and Mysteries." --Book Jacket.
Includes bibliographical references (pages 244-248) and index.
Keywords: English language -- Foreign words and phrases -- Spanish. -- United States; Spanish language -- Influence on English